Cultural Diversity and Students’ Learning Outcomes in Social Science - Tabanao, Eden Grace (Journal of Interdisciplinary Perspectives, 2024)
This study investigates the levels of cultural diversity, learning outcomes in social sciences, and the differences in cultural elements across colleges of the graduating students at Central Philippines State University-Main Campus, Kabankalan City, Philippines. This research problem addresses the need to explore how students' awareness of cultural diversity within their classrooms impacts their academic achievements, particularly their adaptability to diverse learning environments. It also highlights the gap in understanding whether and how culturally responsive teaching strategies can positively affect academic performance, suggesting further investigation to generalize findings and enhance inclusive, effective learning environments. This descriptive-correlational study was designed to establish the relationship between cultural diversity and learning outcomes among 361 students across key areas in Social Sciences. The primary data were derived from examinations administered to the students to assess learning outcomes. A questionnaire consisting of ten-item statements for each component was administered to test the students' levels of cultural diversity. The largest number of respondents was from respondents in the College of Teacher Education, while the lowest number of respondents was from the College of Forestry. The diversity of cultural expressions among colleges manifests the heavy influence of academic settings in the design of students' cultural understanding. The study showed the necessity of more proper cultural diversity training at some colleges, such as Business Education and Teacher Education, where the knowledge of norms and values must be reinforced. The outcomes represented that students from the various colleges are exposed to a good understanding of cultural diversity, although aspects like cultural values and beliefs require improvement. Intercorrelation between the exposure to cultural diversity and the consequences implies that students' views, particularly the social sciences views, grow through greater exposure to cultural diversity.